1996
DOI: 10.1172/jci118439
|View full text |Cite
|
Sign up to set email alerts
|

Murine V lambda x and V lambda x-containing antibodies bind human myelin basic protein.

Abstract: Myelin basic protein (MBP) is highly immunogenic and a known autoantigen capable of inducing experimental allergic encephalomyelitis (EAE), the animal model of multiple sclerosis. We have previously described a murine monoclonal antibody (mAb), F28C4, directed against the encephalitogenic MBP peptide acetyl (Ac) 1-9, which contains a V x light chain. Considering the rarity of V x usage, we determined whether other Abs having V x light chains shared similar antigen (Ag) specificity. We screened a panel of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…As discussed above, we think that DNA and/or MBP binding can result from incomplete editing. For example, the Asp-rich λx editor in association with H chains including 56R binds MBP ( 40 , 41 , and unpublished data). The acidic property of λx to which we attribute the MBP activity is also a feature of κ editors, and these L chains might also confer MBP activity to 56R.…”
Section: Discussionmentioning
confidence: 94%
“…As discussed above, we think that DNA and/or MBP binding can result from incomplete editing. For example, the Asp-rich λx editor in association with H chains including 56R binds MBP ( 40 , 41 , and unpublished data). The acidic property of λx to which we attribute the MBP activity is also a feature of κ editors, and these L chains might also confer MBP activity to 56R.…”
Section: Discussionmentioning
confidence: 94%
“…S2). Interestingly, the heavy chain isotype distribution of Vlx-bearing antibodies in normal mouse serum, upon immunization with myelin basic protein, showed a bias toward g2a and 2b isotypes (47). The heavy chain of Fab RY79-90 belongs also to the IgG2b isotype.…”
Section: Resultsmentioning
confidence: 99%
“…S2). It has been suggested that this unusual light chain confers specificity to the antibodies that contain it (47). As shown below, CDRL3 is a major determinant of antigen recognition.…”
Section: Resultsmentioning
confidence: 99%
“…The mouse λX L-chain has been shown to bind the self-antigen myelin basic protein alone or in combination with V H s (Doyle et al, 2006; Galin et al, 1996). This may account for the low expression of λX observed in wild-type mice (Li et al, 2004).…”
Section: 0 Discussionmentioning
confidence: 99%